PENINGKATKAN PROSES DAN HASIL BELAJAR IPA MENGGUNAKAN MODEL NUMBER HEAD TOGETHER (NHT) DI SEKOLAH DASAR - Aprizan Aprizan; Tri Wiyoko; Titis Wulandari (Jurnal Muara Pendidikan, 2021)
Natural Sciences is a collection of knowledge that is systematically arranged, which includes subjects that are closely related to the natural surroundings, directing the teacher to use the surrounding environment. The problem in this research is the low process and learning outcomes of IPA for fourth grade students at State Elementary School 18/II Tebing Tinggi. So this research aims to improve the process and learning outcomes of students. This study uses the classroom action method, which consists of two cycles. Each cycle consists of planning activities, implementing actions, observing and reflecting. Data collection techniques in this study were observation, tests and documentation. The research subjects were 1 educator and 35 students. The results of this study showed the learning process of educators, the first cycle with an average percentage of 88.8%, the second cycle with an average percentage of 100%. Observation of students during the learning process cycle I with an average percentage of 69.5%, cycle II increased with an average percentage of 87.3%, said to be successful. Based on the results of this study, it can be concluded that the Number Head Together model with the help of image media can improve the learning process and outcomes of students in class IV.